HAMBATAN IMPLEMENTASI SISTEM MANAJEMEN AKUNTABILITAS DI SEKOLAH DASAR NEGERI - Triwiyanto, Teguh; Kusumaningrum, Desi Eri; Sobri, Ahmad Yusuf (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2024)
The aim of this research is to determine the obstacles in implementing an accountability management system in state elementary schools, in the aspects of the curriculum, human resources, educational facilities, school management, students, financing, school environment, and obstacles related to parents. The approach of this research is qualitative research. The location of the research is public elementary schools in Malang City, East Java Province, Indonesia. Purposively, the research sample was determined based on schools that had implemented the Internal Quality Assurance System (IQAS), totaling 22 state elementary schools. Sources of research data are school principals, teachers, and education staff. The data collection involved interviews, focus group discussions, and document analysis. The qualitative data collected were process to ensure reliability and validity. Thematic analysis was used to identify patterns, recurring themes, and variations in participant responses. The research results show various domains that hinder the successful integration of accountability management systems. These obstacles can be categorized into curriculum, human resources, educational facilities, school management, students, financing, school environment, and barriers related to parents